Challenges in part load operation of biogas-based power-to-gas processes (part I) - Gantenbein, Andreas; Schildhauer, Tilman J. (Frontiers in Energy Research, 2022)
Direct methanation of biogas enables the storage of electrical energy in carbon-neutral (bio-)methane and subsequent injection into the national gas distribution grid. The intermittent availability of renewable electricity, as well as the varying nature of biogas production by e.g. anaerobic digestion, necessitate enhanced operational flexibility of such a Power-to-Gas process and intermediate buffer storage. This work provides experimental data of dynamic part load operation of a TRL 5 methanation plant with gas upgrading to grid-ready biomethane. Full recycling of unreacted H2 could be achieved by a commercial biogas upgrading membrane (Evonik SEPURAN® Green). Using real biogas, a sequence of load levels down to 45 % of the full load capacity were tested. Stable operation of the plant could be demonstrated and grid injection limitations could be fulfilled after equilibration of the system. Additionally, an idealised PtG process chain was simulated with the focus on a sensitivity analysis of the H2 storage capacity on the methanation operation hours. It was shown that increasing the hydrogen storage capacity decreases the number of start-up and shut down procedures of the methanation plant. It could be shown that by using an equally sized electrolyser and methanation unit, allowing part load operation of the methanation only during the emptying of the H2 tank leads to longer activity phases of the methanation unit, while allowing part load operation of the methanation reactor during filling of the H2 storage tank had a negative effect.